Uji Aktivitas Antioksidan Ekstrak Metanol Daun Ciplukan menggunakan Metode 2,2-Diphenyl 1-Picrylhydrazyl (DPPH) - Rosa Devitria (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2020)
Utilization of medicines which is natural has become the choice for the people of Indonesia. Various types of plants in Indonesia has been used inherited in the people, but have not used optimally. On the ciplukan tree contain active compounds and have Overcoming various diseases as cancer, rheumatism, coronary heart and cataract is required compound that has antioxidant activity. This research aims to determine the antioxidant activity which is in methanol extract ciplukan leaves. one ofmethod free radical measurement by antioxidant compounds using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method is a method simple antioxidant measurement, fast and doesn't need a lot of reagents. Plants that have potential as a barrier to free radicals is Ciplukan. After being tested from the results of researchin the ciplukan leaf methanol extract obtained IC50 of 820.5695 ppm which means it's very weak but is still recommended as an antioxidant.